Good Government Via E-Procurementsystem (Case Study: Regional Planning and Development of Riau Province) - Novriyanto Novriyanto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
Public procurement in government context involved complicated processes and too budget-consuming.Inadequate and not transparency information are the main factors that cause corruption and data manipulation.However, to avoid such problems, the development of web-based e-procurement system gives priority tointegrity, transparency, accountability, fairness, economy, and efficiency is needed. The e-procurement systemmentioned involved five main modules such as vendor management system, announcing the acquisition of goodand services, electronic access to tender documents, tender submission document, and tender selection. This eprocurementsystem gives privileges to all of the committee members in calculating marks to determine thewinners based on their committee position. Moreover, this e-procurement system can automatically alertimportant events such as the due date of registration, the marking date, and the date of winner announcement.By using this e-procurement system, three stakeholders can see the benefits. First, in term of government sidewhere reducing procurement cost, transparency, time saving, access to new supplier, and blacklist vendor.Second, in term of vendor’s side where reducing cost, accessing to new buyers and increasing sales. Third, interm of public society where adequate information, and public trusts. Hopefully, good governance can beachieved by implementing this e-procurement system.Keyword: e-Procurement, good government